Fundamentals of entrepreneurship (ENT300) : Food truck / Mohammad Gadaffi Abdul Murad ... [et al.] - Abdul Murad, Mohammad Gadaffi; Karim, Mohd Nuralmatusolehin; Abang Abdul Razak, Abang Akmal ‘Irfan; Abang Idham, Abang Muhammad Irfan (2017)
This food truck is offering evening snacks with reasonable price. The reason behind that is they want everyone can afford to buy our products. Other than that, with this food truck, they are trying to make their customer’s day easier by showing concept “food will find you not you find the food” Other than that, this food truck also bring creativity in food so that it can change the people’s mentality that “street food” is just food in ordinary night market.Food truck market target are the people near this Kota Samarahan but to be more specific in Desa Ilmu. It is because Desa Ilmu has the night market every Friday and Saturday night. Night market near Desa Ilmu attracting people who lives in Kota Samarahan to buy food, stuff and etc. Furthermore, Desa Ilmu is adjacent to UiTM campus Samarahan, so the students in UiTM area is also our market target.